Little Wynwood: whiteness, tourism, and gentrification in Havana's San Isidro neighborhood. Issue 2 (3rd April 2023) - Speakman, Maile
ABSTRACT: Through an analysis of an Airbnb Experience called 'Paint a graffiti with Havana Street Art' in San Isidro, a majority non-white and economically marginalized neighborhood in the southern part of Havana's colonial city, I interrogate how whiteness is transforming San Isidro in the image of Wynwood, Miami. I do so by tracing the mobility and barriers to movement of international graffiti artists, tour guides, tourists, and hosts, showing how whiteness works as an economic, social, and historical structure that marks people by neighborhood of origin, family inheritance, proximity to foreign capital, and ability to move seamlessly between multiple local and international geographies. I argue that outside protagonists in San Isidro understand the neighborhood through this structure of whiteness, viewing the neighborhood as a settler frontier of capital extraction but also as a site of emotional and artistic self-discovery where they can 'make their mark.'